If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=8+y/2
We move all terms to the left:
-6-(8+y/2)=0
We add all the numbers together, and all the variables
-(y/2+8)-6=0
We get rid of parentheses
-y/2-8-6=0
We multiply all the terms by the denominator
-y-8*2-6*2=0
We add all the numbers together, and all the variables
-1y-28=0
We move all terms containing y to the left, all other terms to the right
-y=28
y=28/-1
y=-28
| 3(n-4)=24 | | 10z+4=295z+80-12 | | 5(-2/7x+2)=80/7 | | 3x+67=100 | | (8.7^x)-83=0 | | 12-2n=1 | | 9x-4=2x-4 | | 180=6y-2+90 | | 24=-4/7b | | 6+8(x2)=6x | | 65=20(x-5) | | (x-3)8-9=-25 | | 2=6(y-2) | | 49+x^2=(x^2+2x+1) | | 119/45=13/9-6/5r | | N/5=2n+9 | | 8k+16=6k | | 3(x+8)^2=9x^2+144x+48 | | -5/8x+10x=-8 | | 5x-5=18-10x | | 3-5v=-42 | | x(2x-7)=130 | | 9=7-x/2 | | -4x+7x=1 | | 8x2=2x+15 | | 2145/14+x=82.5 | | (x+40)+(2x-22)=180 | | -3+2x=-4x+11+9x-2 | | 2-x+4=11 | | 2/3n-1=3 | | (3x^2)-9x-56=0 | | 2(3m-4)+3(2m-3)=-2(m+5) |